Augmented Reality Technology (ART) in Science Education and Engineering Technology: A Review - Netragaonkar, Yashpal D.; Lokhande, Netra; Khanna, Devesh; Kishan, Shubham (Journal of Engineering Education Transformations, 2025)
This paper provides a comprehensive analysis of Augmented Reality Technology (ART) in Science Education and Engineering Technology. Science Education and Engineering Technology go hand in hand as without scientific studies applications cannot exist. The term science is well known for knowledge-based society. It has a vast scope in this world. In every step of human life, the terms Science and Technology are both the two sides of one coin. The main objectives of this review are to - 1. Understand the concept of Augmented Reality Technology (ART). 2. Identify the different types of Augmented Reality Technology (ART). 3. Find out the correlation between Augmented Reality Technology (ART) and Science Education. 4. Identify the various strategies of Augmented Reality Technology (ART) for Science Education. The rising prominence of Augmented Reality (AR) technology stems from its ability to deliver captivating and interactive experiences to users. The current landscape of AR technology is characterized by its dynamic and fast-paced evolution, with numerous applications emerging across industries like gaming, retail, education, and healthcare. By overlaying digital content onto the physical world, AR technology creates a blended reality environment that offers engaging and immersive experiences to users. In particular, AR has the potential to revolutionize the methods through which students comprehend and interact with scientific and engineering concepts. It presents an opportunity for future research to delve deeper into exploring the extensive capabilities of this technology and unlock its full potential in educational contexts.